APPLIED ECONOMIC-MATHEMATICAL ANALYSIS OF FIRE-RESISTANT PRODUCTS SINTERING PROCESSES: EFFICIENCY MANAGEMENT OF PRODUCTION PLANS PJSC «ZAPORIZHVOGNETRYV» - Glushchevsky, Vyacheslav; Ogloblina, Viktoriia; Zhyliakov, Oleg; Khrapkin, Oleksandr (Scientific Journal "Metallurgy", 2024)
The article addresses the problem of applied economic-mathematical analysis of interrelated processes in the production, sintering, and material-resource support of fire-resistant product manufacturing. A conceptual approach to modeling the distribution of raw materials for obtaining an optimal charge is substantiated, considering the criterion of minimizing the total production cost of material and raw material expenses for fulfilling the order portfolio of PJSC «Zaporizhvognetryv». The author's modeling concept is based on the principles of a systemic approach, employing research methods such as economic-mathematical modeling, correlation-regression analysis, and groups of statistical data processing and summarization methods. This is used to create and implement a modeling toolkit – a complex of economicmathematical and information models of a specific structure (developed in MS Excel electronic spreadsheets). These models collectively realize the functionality of the "Charge Optimization" and "Raw Material Price Forecasting" modules. This ensures effective operational and tactical regulation and management of the efficiency of production plans at the level of the main links of the production activities of PJSC «Zaporizhvognetryv». A human-machine dialogue procedure has been developed for calculating the demand for raw materials in conditions of multivariate combinations of acceptable rational variants of charges. To implement this procedure, an integrated information model was developed on the MS Excel platform, automating decision support for the distribution of charge materials among different charge variants for the production of fire-resistant products, in compliance with technological norms and aligned with the volume of the planned order portfolio of PJSC «Zaporizhvognetryv». The proposed mathematical and informational support enables the automated operational verification of the compiled production plan for its resource balance and adherence to contractual business obligations through a dialog system on the MS Excel platform, using the developed economicmathematical model for charge optimization. The directions for applied economic-mathematical analysis of management decisions based on the developed toolkit are outlined. The modelalgorithmic complex was tested on the statistical data of PJSC «Zaporizhvognetryv» to assess the effectiveness of the compiled production plan (planning horizon – one month). The obtained economic effect is justified, indicating a conditional reduction in total costs (model calculations) by 8,6 million UAH compared to actual expenses. This allowed practical recommendations to be made for further improvement of the efficiency management of production plans for PJSC «Zaporizhvognetryv» based on the calculations.